Cuidados paliativos de enfermería en paciente con cáncer de cuello uterino estadio iiib: un estudio de caso - Viteri Huertas, Eduardo Israel (2024)
Carcinoma of the cervix is currently the second leading cause of cancer death in women worldwide, which makes it a major health problem. Thus, in terminal stages, palliative care should be initiated from the moment of diagnosis and adapted during the course of the disease. For this reason, the present case study focused on determining nursing interventions focused on palliative care in the patient with stage IIIB cervical cancer, through nursing instruments that contribute to the optimization of her quality of life. Therefore, tools such as the palliative functional scale were used, identifying a level of 40% in her functionality, the Marjory Gordon patterns that allowed the analysis of the relevant aspects affected at the level of the cognitive perceptual pattern, nutritional metabolic pattern and exercise activity pattern. Likewise, the use of the Barthel index was considered, obtaining a total sum of 35 points, which translates into a degree of severe dependence in the performance of daily activities. Finally, based on the prioritization of needs, the NANDA, NOC and NIC taxonomies were used to design proposals for nursing care plans that were based on chronic pain due to terminal catastrophic illness with the use of pharmacological therapy; addressing nutritional imbalance: lower than body needs to bring the patient to a moderately compromised state; addressing impaired physical mobility; and preventing the risk of infection due to the presence of percutaneous nephrostomy.